Preliminary Evaluation of the Implementation of a Routines-Based Early Childhood Intervention Model in Australia: Practitioners' Perspectives. (May 2016) - Hughes-Scholes, Carolyn H.; Gatt, Sarah L.; Davis, Kate; Mahar, Nicole; Gavidia-Payne, Susana
The aim of the current pilot study was to evaluate the implementation of a routines-based early childhood intervention (RBECI) model by Australian Early Childhood Intervention (ECI) professionals. The RBECI model consisted of four key components: (a) Routines-Based Interviews (RBIs), (b) participation-based goals, (c) home visits, and (d) community consultations. Five ECI professionals and nine families were recruited from an Australian ECI service. Professionals' ability to implement the model was assessed immediately before and 6 months after receiving training in the model. Individual in-depth interviews elicited professionals' perspectives on implementing the model. Results revealed that professionals' knowledge, understanding, confidence, and home visiting skills increased from pre- to post-intervention, but community consultation skills did not. There were limitations in the quality of RBIs and participation-based goals produced. Overall, professionals were positive about the implementation of the model. The findings provide support for the adoption of the RBECI model in ECI more broadly.